2020
DOI: 10.1021/acsapm.0c00147
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Route to Prepare Polypyrrole-Coated Filter Papers via Vapor Phase Polymerization and Their Gas Sensing Application

Abstract: Vapor phase polymerization has been used for the synthesis of polypyrrole-coated filter paper (PPy-FP) using a simple experimental setup. In addition, we have doped the polymer-coated filter papers with hydrochloric acid (HCl), camphorsulfonic acid (CSA), and p-toluenesulfonic acid (PTSA) to prepare HCl-PPy-FP, CSA-PPy-FP, and PTSA–PPy-FP, respectively. These samples were characterized by scanning electron microscopy (SEM), thermogravimetric analysis (TGA), attenuated total reflectance–Fourier transform infrar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 61 publications
(103 reference statements)
0
23
0
Order By: Relevance
“…The term VPP is used interchangeably with vapor deposition polymerization 95 . Majumdar et al 96 and Hanif et al 97 described VPP as an easy, inexpensive, and effective method of depositing CP coating onto a particular substrate. The main advantage of VPP is that it is a solvent‐free synthesis in which the monomers are applied as vapor rather than a solution, and no liquid acts as transport medium for particle agglomeration 94,95,98 .…”
Section: Synthesis Of Ppymentioning
confidence: 99%
See 3 more Smart Citations
“…The term VPP is used interchangeably with vapor deposition polymerization 95 . Majumdar et al 96 and Hanif et al 97 described VPP as an easy, inexpensive, and effective method of depositing CP coating onto a particular substrate. The main advantage of VPP is that it is a solvent‐free synthesis in which the monomers are applied as vapor rather than a solution, and no liquid acts as transport medium for particle agglomeration 94,95,98 .…”
Section: Synthesis Of Ppymentioning
confidence: 99%
“…The PPy‐coated fabrics show a surface resistance of 0.5–0.8 kΩ/cm. Meanwhile, Majumdar et al 96 fabricated PPy‐coated filter paper (FP) doped with HCl, CSA, and PTSA by using VPP method. Initially, FP (substrate) is soaked in 0.1 M FeCl 3 solution for 15 min followed by drying at room temperature.…”
Section: Synthesis Of Ppymentioning
confidence: 99%
See 2 more Smart Citations
“…et al explored the effect of inorganic and organic acid dopants on ammonia and other VOC sensing performance of PPy nanoparticles coated filter papers. [19] According to the experimental facts, research groups revealed that the nature of electrolyte solution and salt concentration during PPy polymerization also play a pivotal role in the ammonia sensing phenomenon. [20] Most of these researchers introduced the PPy as a selective solid-state sensor material and humidity doesn't affect the measurement of ammonia.…”
Section: Introductionmentioning
confidence: 99%